Ability to Apply (JIT) Technology To Implement Strategy and Achieve Customer Satisfaction Application Study In The General Company For Electrical and Electronic Industries - Abbas Nawar Al-Musawi; Mohammed Alwan (Journal of Madenat Alelem University College, 2019)
Research problem deals with Iraqi industrial and economic units which are unable to use appropriate accounting systems correctly which concerned with costs management and the modern productive strategies to deliver the services to the customer, whether expected or not for him to satisfy his needs. It even goes beyond that to satisfy his pleasure and gladness. The research also aims to determine the extent to which the Iraqi industrial economic units apply to modern and modern methods and techniques and to use them in providing the appropriate information needed to support Agile manufacturing strategy and achievement of customer satisfaction. The study depends on the following basic hypotheses:                                                                                                        “Using techniques of Agile manufacturing strategy in production and costs management help to achieve satisfaction of customer”.“It's possible to submit a suggestion to apply techniques of Agile manufacturing strategy in Iraqi industrial and economic environment”.     The researcher chose the General Company for Electrical and electronic industries to achieve research goal and testing his hypotheses which are applied to the Motors plant, as well as submit a suggestion for applying in economic unit. The study adopted measurement methods and empirical analysis through using analytic mod. The research inferred many conclusions, the most important ones are: as well as it's possible to submit a suggestion to apply techniques of Agile manufacturing strategy in Iraqi industrial and economic environment.